Investigation of temperature distribution and performance of SOFC short stack with/without machined gas channels. (22nd June 2016) - Canavar, Murat; Mat, Abdullah; Celik, Selahattin; Timurkutluk, Bora; Kaplan, Yuksel
Abstract: Solid oxide fuel cells (SOFCs) generate clean energy via electrochemical reactions at high operating temperatures. The distribution of the electrochemical reactions in the cell depends on the flow field design of the interconnectors. The non-uniform distribution of the reactions due to the flow field design may cause the development of thermal stresses which may lead to micro or macro cracks in the cell and thus a significant performance loss even a cell failure. In this study, the effects of operating current densities and fuel flow rates on the temperature profile within the cell and the cell performance are experimentally investigated for two different flow-field designs with Crofer 22 APU interconnectors, i.e. Design I and Design II. Design I, which mimics the conventional interconnector structure, has machined gas channels and porous nickel mesh at the anode side for the distribution of hydrogen and the collection of the current generated in the cell while at the anode side of Design II, only wire woven nickel mesh is employed. The experimental results indicate that Design II provides much more uniform temperature distributions under 20–40 A current loads and 1–2 NL/min H2 flow rates when compared to those of Design I. Furthermore, Design II exhibits a higher peak power density than Design I at an operation temperature of 800 °C. Highlights: Woven meshes as a flow-field instead of the conventional channels to reduce the cost. Temperatures measurements are performed for mesh-based and parallel channels based flow field. Relatively a uniform fuel distribution achieved by the woven nickel. The highest temperatures for both designs seem to occur at the zones close to the exit sections. The maximum temperatures increase with increasing the operating current for all measurement points.